Fluid-structure-interaction modeling of dynamic fracture propagation in pipelines transporting natural gases and CO2-mixtures. (August 2019) - Keim, V.; Marx, P.; Nonn, A.; Münstermann, S.
Abstract: As part of current design standards, the Battelle Two-Curve Model (BTCM) is still widely used to predict and secure ductile crack arrest in gas transmission pipelines. For modern linepipe steels and rich natural gases or CO2 mixtures, the BTCM might lead to incorrect predictions. On the one hand, it suffers from the insufficient description of the individual physical processes in the pipe material and fluid itself. Furthermore, the model does not account for fluid-structure-interaction (FSI) effects during simultaneous running-ductile fracture (RDF) and mixture decompression. Numerical FSI models allow for a more sophisticated, coupled analysis of the driving forces for the failure of pipelines. This paper deals with the development of an FSI model for the coupled prediction of 3D pressure profiles acting on the inner pipe wall during crack propagation. The coupled Euler-Lagrange (CEL) method is used to link the fluid and structure models. In a Lagrange formulation, the modified Bai-Wierzbicki (MBW) model describes the plastic deformation and ductile fracture as a function of the underlying stress/strain conditions. The fluid behavior is calculated in a 3D model space by Euler equations and the GERG-2008 reference equation of state (EOS). The coupled CEL model is used to predict the RDF in small-diameter pipe sections for different fluid mixtures. The calculated 3D pressure distributions ahead and behind the running crack tip (CT) significantly differ in axial and circumferential directions depending on the mixture composition. The predicted FSI between the pipe wall and fluid decompression in 3D CEL/FSI model provides reliable knowledge about the pressure loading of the pipeline during RDF. Highlights: A methodology for the coupled description of 3D fluid-structure-interaction effects during running ductile fracture in pipelines was developed. The modified Bai-Wierzbicki (MBW) model describes the pipe material in a Lagrange framework. The GERG-2008 equation of state is applied for the description of the volumetric behavior of natural gases and CO2 mixtures. Fluid-structure interactions are modeled in the coupled Euler Lagrange (CEL) framework. 3D pressure profiles are numerically predicted to study the influence of different mixtures' decompression in the fracture propagation in small-diameter pipes.